High-thermal-conductivity corona-resistant electromagnetic shielding composite aramid insulation paper, preparation method and application
By using coaxial nanofiber filaments of meta-aramid fibers and carbon nanotubes combined with the composite structure of mica nanosheets and fluorinated graphene, the lack of performance of traditional insulating paper in high temperature, high frequency and electromagnetic sensitive environments is solved, and composite aramid insulating paper with high thermal conductivity, corona and electromagnetic shielding is achieved.
Patent Information
- Application Number
- CN202411731194.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Traditional insulating paper cannot meet the insulating medium requirements of advanced electrical equipment in high temperature, high frequency pulse, strong electric field and electromagnetic sensitive environment, and there are problems of insufficient thermal conductivity, corona resistance and electromagnetic shielding performance.
Meta-aramid fibers are used as the shell layer and carbon nanotubes are core layers to obtain coaxial nanofiber wires by coaxial electrospinning. Combined with mica nanosheets, fluorinated graphene and meta-nanoaramid fibers, composite aramid insulating paper is formed by vacuum suction filtration and hot pressing treatment.
It realizes the high thermal conductivity, corona and electromagnetic shielding performance of composite aramid insulating paper, and can meet the insulating media needs of advanced electrical equipment in a variety of harsh application scenarios.
Smart Images

Figure CN119626686A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of insulating materials, and in particular to a high-thermal-conductivity, corona-resistant, electromagnetic-shielding composite aramid insulating paper, a preparation method and an application thereof. Background Art
[0002] Reliable insulation is the cornerstone of the safe and stable operation of ultra-high voltage transmission networks. The rational use of insulating materials with electromagnetic shielding functions in ultra-high voltage transformers, reactors and other electrical appliances can optimize the electric field distribution and achieve a significant improvement in the overall insulation effect. As the core equipment in the power system to complete important tasks such as voltage conversion and power distribution, the improvement of the energy efficiency of the transformer has an important impact on the energy efficiency optimization of the entire power system. In the transformer, the winding leakage flux will produce large eddy current losses after entering the steel box wall, which becomes a major obstacle to further reducing the transformer loss. The electromagnetic shielding materials with excellent performance can effectively reduce the leakage flux entering the box wall and reduce the eddy current loss of the transformer. In addition, although the rapid development of electrical equipment and power electronics technology has promoted social progress, it has also brought about increasingly serious electromagnetic interference problems. These interferences will not only affect the normal operation of the equipment, but may also have adverse effects on the surrounding environment and other electronic equipment, and must be effectively shielded.
[0003] Although the current development of high-power, high-frequency and integrated advanced electrical equipment has brought many conveniences and progress to production and life, it has also caused serious problems such as equipment heat accumulation and high-frequency impact corona discharge, which has caused serious safety hazards to the stable and reliable operation of electrical equipment. As an insulating medium widely used in electrical equipment such as motors, reactors, and bushings, the thermal conductivity, corona resistance and mechanical strength of traditional insulating paper can no longer meet the current development needs of electrical equipment. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a high-thermal-conductivity, corona-resistant, electromagnetic-shielding composite aramid insulation paper, a preparation method and an application thereof.
[0005] The technical solution adopted by the present invention is: a method for preparing a high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper, comprising the following steps:
[0006] Step 1: Using meta-aramid fiber as the shell layer and carbon nanotube as the core layer, coaxial nanofiber filaments are obtained by coaxial electrospinning;
[0007] Step 2: fully mixing mica nanosheets, fluorinated graphene and meta-nano aramid fibers in a solvent to obtain a mixed slurry; the mass ratio of the mica nanosheets, fluorinated graphene and meta-nano aramid fibers is 0.1-0.3:0.1-0.2:1;
[0008] Step 3: preparing a nanofiber felt using the coaxial nanofibers obtained in step 1;
[0009] Step 4: Using the nanofiber felt obtained in step 3 as the interlayer material and the mixed slurry as the surface material, a multilayer structure material is formed by vacuum filtration, wherein the upper and lower surfaces of the interlayer material are covered with the surface material;
[0010] Step 5: hot-press the multilayer structure material obtained in step 4 to obtain the desired composite aramid insulation paper.
[0011] Furthermore, in step 1, the diameter of the coaxial nanofiber filament is 200-600 nm, and the ratio of the radius of the core layer to the thickness of the shell layer in the coaxial nanofiber filament is 2-5:8-5.
[0012] Furthermore, the intermediate aramid fiber in step 1 needs to be pretreated before use:
[0013] Cutting the meta-aramid fibers into short fibers of 5 to 10 mm;
[0014] The chopped fibers were ultrasonically treated in acetone, then vacuum filtered and rinsed three times, and then dried. After drying, the fibers were dissolved in a LiCl solution to obtain a meta-aramid fiber solution.
[0015] Furthermore, the preparation method of mica nanosheets in step 2 is as follows:
[0016] Adding mica powder to the intercalant solution, and obtaining a mica dispersion after ultrasonic treatment;
[0017] The mica dispersion was heated at 100°C for 6 hours; after centrifugal rinsing, it was dried under vacuum conditions;
[0018] The preparation process of meta-nano aramid fiber is as follows:
[0019] Cutting the meta-aramid fibers into short fibers of 5 to 10 mm;
[0020] The chopped fibers were ultrasonically washed in acetone, then vacuum filtered and rinsed three times, and then dried;
[0021] The dried meta-aramid fiber is dissolved in a strong alkaline solution, fully stirred, and subjected to ultrasonic dispersion treatment.
[0022] Furthermore, the mixed slurry preparation process in step 2 is as follows:
[0023] Add mica nanosheets and fluorinated graphene into the solvent dimethyl sulfoxide and perform water bath sonication;
[0024] adding meta-nano aramid fiber dispersion;
[0025] Deionized water is dropped into the mixed solution, and ultrasonic treatment is performed in a water bath to obtain a mixed solution;
[0026] The mixed solution after ultrasonication is injected into deionized water to generate floccules;
[0027] The flocculants are dispersed in deionized water and sheared at high speed to obtain a dispersed and stable mixed slurry.
[0028] Furthermore, in step 4, the mass ratio of the surface layer material to the interlayer material is 7-9:3-1.
[0029] Furthermore, the hot pressing process in step 5 is as follows:
[0030] First, hot pressing was performed at a pressure of 12 MPa and a temperature of 180°C for 6 min;
[0031] Then, the pressure was maintained at 12 MPa at room temperature for 2 min.
[0032] A high thermal conductivity, corona-resistant and electromagnetic shielding composite aramid insulation paper, wherein the composite aramid insulation paper is a composite sandwich structure formed by hot pressing with an outer layer material covering the upper and lower surfaces of the sandwich material;
[0033] The sandwich material is a composite nanofiber felt prepared by coaxial nanofiber filaments obtained by coaxial electrospinning, with meta-aramid fibers as the shell layer and carbon nanotubes as the core layer;
[0034] The outer layer material is a mixed slurry obtained by fully mixing and dispersing mica nanosheets, fluorinated graphene and meta-nano aramid fibers.
[0035] Furthermore, the carbon nanotubes have a length of 0.4 to 5 μm and a diameter of 8 to 20 nm; the mica nanosheets have a particle size of 300 to 600 nm and a thickness of 100 to 200 nm; the fluorinated graphene has a single-layer structure, a fluorine-carbon ratio of 1:1, a particle size of 4 to 8 μm, and a thickness of 1 to 2 nm.
[0036] The invention discloses an application of high thermal conductivity, corona resistance and electromagnetic shielding composite aramid insulation paper, wherein the composite aramid insulation paper is used for preparing insulation parts of power transformers.
[0037] The beneficial effects of the present invention are:
[0038] The composite aramid insulation paper obtained by the present invention has excellent thermal conductivity, corona resistance and electromagnetic shielding properties, and can meet the needs of advanced power electronic devices and electrical equipment for insulating media in various harsh application scenarios such as high temperature, high frequency pulses, strong electric fields, and electromagnetic sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1The figure is a schematic diagram of the structure of the composite aramid insulation paper obtained by the present invention.
[0040] Figure 2 It is a schematic diagram of the structure of the coaxial nanofiber filaments in the present invention.
[0041] Figure 3 This is a scanning electron microscope (SEM) image of the interlayer material obtained in step 4 of Example 1 of the present invention.
[0042] Figure 4 It is a schematic diagram comparing the breakdown strength of the composite aramid insulation paper obtained in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention.
[0043] Figure 5 It is a schematic diagram comparing the corona resistance time of the composite aramid insulation paper obtained in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention.
[0044] Figure 6 It is a schematic diagram comparing the electromagnetic shielding effectiveness of the composite aramid insulation paper obtained in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention.
[0045] Figure 7 It is a schematic diagram comparing the thermal conductivity of the composite aramid insulation paper obtained in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention.
[0046] Figure 8 It is a schematic diagram comparing the mechanical tensile strain-stress curves of the composite aramid insulation paper obtained in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention.
[0047] In the figure: 1-outer layer material, 2-sandwich material, 3-meta-aramid fiber shell layer, 4-carbon nanotube core layer. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0049] A method for preparing high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper comprises the following steps:
[0050] Step 1: Using meta-aramid fiber as the shell layer and carbon nanotube as the core layer, coaxial nanofiber filaments are obtained by coaxial electrospinning;
[0051] First, the meta-aramid fiber is pretreated:
[0052] Cutting the meta-aramid fibers into short fibers of 5 to 10 mm;
[0053] The chopped fibers were ultrasonically treated in acetone, then vacuum filtered and rinsed three times, and then dried. After drying, the fibers were dissolved in a LiCl solution to obtain a meta-aramid fiber solution.
[0054] The length of the carbon nanotube is 0.4-5 μm, and the diameter is 8-20 nm; the diameter of the coaxial nanofiber is 200-600 nm, and the ratio of the radius of the core layer to the thickness of the shell layer in the coaxial nanofiber is 2-5:8-5. The diameter of the coaxial nanofiber and the ratio of the radius of the core layer to the thickness of the shell layer are controlled by controlling the parameters of electrospinning, and are specifically set according to actual needs, as long as they are within this range.
[0055] Step 2: fully mixing mica nanosheets, fluorinated graphene and meta-nano aramid fibers in a solvent to obtain a mixed slurry; the mass ratio of the mica nanosheets, fluorinated graphene and meta-nano aramid fibers is 0.1-0.3:0.1-0.2:1;
[0056] The preparation method of mica nanosheets is as follows:
[0057] Adding mica powder to the intercalant solution, and obtaining a mica dispersion after ultrasonic treatment;
[0058] The mica dispersion was heated at 100°C for 6 hours; after centrifugal rinsing, it was dried under vacuum conditions;
[0059] The preparation process of meta-nano aramid fiber is as follows:
[0060] Cutting the meta-aramid fibers into short fibers of 5 to 10 mm;
[0061] The chopped fibers were ultrasonically washed in acetone, then vacuum filtered and rinsed three times, and then dried;
[0062] The dried meta-aramid fiber is dissolved in a strong alkaline solution, fully stirred, and subjected to ultrasonic dispersion treatment.
[0063] The particle size of mica nanosheets is 300-600nm, and the thickness is 100-200nm; the fluorinated graphene is a single-layer structure, the fluorine-carbon ratio is 1:1, the particle size is 4-8μm, and the thickness is 1-2nm.
[0064] The mixed slurry preparation process is as follows:
[0065] Add mica nanosheets and fluorinated graphene into the solvent dimethyl sulfoxide and perform water bath sonication;
[0066] adding meta-nano aramid fiber dispersion;
[0067] Deionized water is dropped into the mixed solution, and ultrasonic treatment is performed in a water bath to obtain a mixed solution;
[0068] The mixed solution after ultrasonication is injected into deionized water to generate floccules;
[0069] The flocculants are dispersed in deionized water and sheared at high speed to obtain a dispersed and stable mixed slurry.
[0070] Step 3: preparing a nanofiber felt using the coaxial nanofibers obtained in step 1;
[0071] Step 4: Using the nanofiber felt obtained in step 3 as the interlayer material and the mixed slurry as the surface material, a multilayer structure material is formed by vacuum filtration, wherein the upper and lower surfaces of the interlayer material are covered with the surface material;
[0072] The mass ratio of the surface material to the interlayer material is 7-9:3-1.
[0073] Step 5: hot-press the multilayer structure material obtained in step 4 to obtain the desired composite aramid insulation paper.
[0074] The hot pressing process is as follows:
[0075] First, hot pressing was performed at a pressure of 12 MPa and a temperature of 180°C for 6 min;
[0076] Then, the pressure was maintained at 12 MPa at room temperature for 2 min.
[0077] The composite aramid insulation paper is a composite sandwich structure formed by hot pressing with the upper and lower surfaces of the sandwich material covered with outer materials. Figure 1 As shown;
[0078] The sandwich material is a composite nanofiber felt prepared by coaxial nanofiber filaments obtained by coaxial electrospinning with meta-aramid fiber as the shell layer and carbon nanotube as the core layer; the coaxial nanofiber filament structure is as follows Figure 2 shown.
[0079] The outer layer material is a mixed slurry obtained by fully mixing and dispersing mica nanosheets, fluorinated graphene and meta-nano aramid fibers.
[0080] Example 1
[0081] A method for preparing high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper comprises the following steps:
[0082] Step 1: Using meta-aramid fiber as the shell layer and carbon nanotube as the core layer, coaxial nanofiber filaments are obtained by coaxial electrospinning;
[0083] First, the meta-aramid fiber is pretreated:
[0084] The meta-aramid fiber filaments are mechanically sheared into short fibers with a length of 5 to 10 mm, and then the short fibers are immersed in acetone and subjected to 300 W water bath ultrasound for 72 hours to wash away stains. After filtering off the acetone, the short fibers are soaked in anhydrous ethanol for 12 hours, followed by vacuum filtration and rinsing with anhydrous ethanol and then with deionized water for 3 times each. Finally, the rinsed fibers are vacuum dried at 60°C for at least 5 days for use.
[0085] Weigh 1.6 g of anhydrous LiCl and stir it thoroughly in 80 g of DMAc until it is completely dissolved. Weigh 20 g of pretreated meta-aramid fiber and add it to the solution. Seal and stir in a water bath at 80°C until a uniform transparent solution is formed. Finally, keep the prepared meta-aramid fiber solution sealed and place it at room temperature for 24 hours to degas.
[0086] Preparation of carbon nanotube dispersion: 3 g carbon nanotubes and 2 g DMAc were weighed into a test tube, the mouth of the test tube was sealed with a sealing film, and ultrasonicated in a 60 W water bath at room temperature until there was no visible precipitation at the bottom of the test tube and a stable Tyndall effect was observed when the dispersion was irradiated with a laser.
[0087] Select 18G stainless steel needle (inner diameter 1.00mm) as the outer needle and 24G stainless steel needle (inner diameter 0.30mm) as the inner needle to assemble the electrostatic coaxial spinning needle. The carbon nanotube dispersion and meta-aramid fiber dispersion are sucked into two 10mL syringes respectively, and the syringe containing the carbon nanotube dispersion is connected to the inner needle, and the syringe containing the meta-aramid fiber dispersion is connected to the outer needle to ensure no dripping or leakage. Subsequently, the two syringes are placed in the injection pump push position, the electrostatic spinning machine power is turned on, the distance between the spinning head and the drum receiver is set to 15cm, the spinning voltage is 18kV, the drum receiver speed is 200rpm, the ambient temperature is 25℃, the humidity is 40RH%, the injection speed of the inner needle of the injection pump is 0.10~0.15mL / h, and the injection speed of the outer needle is 0.45~0.60mL / h, so that the liquid at the needle does not drip and the spinning is not interrupted.
[0088] After the electrospinning is completed, preliminary drying is performed to remove the incompletely volatilized DMAc solvent. The steps are as follows:
[0089] The coaxial aramid fiber filaments prepared by the coaxial spinning process were carefully peeled off from the receiving roller to avoid bending and breakage, and then spread on a glass plate and placed in a constant temperature vacuum drying oven at 60°C and 0.1 bar for drying for 48 hours.
[0090] Step 2: fully mixing mica nanosheets, fluorinated graphene and meta-nano aramid fibers in a solvent to obtain a mixed slurry; the mass ratio of the mica nanosheets, fluorinated graphene and meta-nano aramid fibers is 0.1-0.3:0.1-0.2:1;
[0091] The preparation process of mica nanosheets is as follows:
[0092] Weigh 1 g of anhydrous lithium citrate as an intercalant, fully stir in 60 g of deionized water until completely dissolved, and add 1 g of natural mica powder with an average particle size of 20 μm and 40 g of isopropanol to the lithium citrate aqueous solution;
[0093] Then, the mica dispersion was placed under 200W, 40kHz water bath ultrasound for 30 minutes to obtain a uniformly dispersed mica dispersion. The mica dispersion was poured into a hydrothermal reactor lined with polytetrafluoroethylene and hydrothermally reacted at 100°C for 6 hours.
[0094] After the hydrothermal reaction is completed, the peeled mica nanosheets are poured out of the hydrothermal reactor, and centrifuged and rinsed at least 5 times with 50 mL of deionized water at 2000-25000 rpm each time, and the rinsed mica nanosheet powder is placed at 60° C. and 0.1 bar vacuum environment and dried for 72 hours.
[0095] The preparation process of meta-nano aramid fiber is as follows:
[0096] The meta-aramid fiber filaments were mechanically cut into short fibers with a length of 5 to 10 mm, and the short fibers were soaked in acetone and subjected to 300W water bath ultrasound for 72 hours to remove stains. After filtering off the acetone, the short fibers were soaked in anhydrous ethanol for 12 hours. Subsequently, the fibers were vacuum filtered and rinsed with anhydrous ethanol and then with deionized water for three times each, and the rinsed fibers were vacuum dried at 60°C for at least 5 days for use.
[0097] Weigh 4.8g of KOH into a brown silk-mouth bottle, add about 20mL of deionized water and stir until KOH is completely dissolved. Then add 1000mL of DMSO and mix thoroughly to obtain a DMSO concentrated alkali solution. Finally, add 3.2g of pretreated meta-aramid fiber to the DMSO concentrated alkali solution, seal the bottle mouth, and stir at 800rpm in a dark environment at 20℃ for 7 days to finally obtain a dark red nano-aramid fiber dispersion.
[0098] Take 620mL of DMSO solvent, add 0.15g of mica nanosheets and 0.1g of fluorinated graphene, and perform water bath ultrasonic treatment for 30min; then add 310mL of nano-aramid fiber dispersion; drop 10mL of deionized water into the mixed solution, perform water bath ultrasonic treatment for 3h, and then quickly inject the prepared mixed solution into 1000mL of deionized water to generate a flocculant; repeatedly wash the flocculant with a Buchner funnel, filter out the residual solvent, disperse the flocculant in 500mL of deionized water, and high-speed shear at a speed of 12000rpm for 20min to obtain a dispersed and stable slurry as the outer layer material.
[0099] Step 3: preparing a nanofiber felt using the coaxial nanofibers obtained in step 1;
[0100] Step 4: Using the nanofiber felt obtained in step 3 as the interlayer material and the mixed slurry as the surface material, a multilayer structure material is formed by vacuum filtration, wherein the upper and lower surfaces of the interlayer material are covered with the surface material;
[0101] Take an appropriate amount of the outer layer material in step 2 so that the quantitative ratio of the outer layer material to the interlayer material is 8:2, divide the outer layer material slurry into 2 parts, pour any one of the outer layer material slurry into a suction filtration bottle, use the nanofiber felt obtained in step 3 as a filter membrane, vacuum filter until the outer layer material slurry in the suction filtration bottle is dry, and make the solids in the slurry completely deposited on the surface of the filter membrane. Then turn the composite nanofiber felt filter membrane over, and filter the other outer layer material in the same way until it is dry, and a multilayer structure material can be obtained.
[0102] Step 5: hot-press the multilayer structure material obtained in step 4 to obtain the desired composite aramid insulation paper.
[0103] The multilayer structure material obtained in step 4 is placed in the pressure plate of the hot press, and the hot pressing pressure is set to 12 MPa; during the hot pressing process, first hot press at 180°C for 6 minutes, then return to room temperature and cold press for 2 minutes to obtain the desired composite aramid insulation paper.
[0104] Example 2
[0105] The other steps of this embodiment are the same as those of Embodiment 1, except that in step 4, the quantitative ratio of the outer layer material to the interlayer material is 9:1.
[0106] Example 3
[0107] The other steps of this embodiment are the same as those of Embodiment 1, except that in step 4, the quantitative ratio of the outer layer material to the interlayer material is 7:3.
[0108] Example 4
[0109] The other steps of this embodiment are the same as those of Embodiment 1, except that in Step 2, the masses of the mica nanosheets and the fluorinated graphene are 0.3 g and 0.15 g, respectively.
[0110] Example 5
[0111] The other steps of this embodiment are the same as those of Embodiment 1, except that in Step 2, the masses of the mica nanosheets and the fluorinated graphene are 0.2 g and 0.2 g, respectively.
[0112] Comparative Example 1
[0113] The difference between this comparative example and Example 1 is that step 1 is not included, and the process of step 3 is as follows: 620 mL of DMSO solvent is taken, 0.30 g of carbon nanotubes is added thereto, and water bath ultrasonic treatment is performed for 30 minutes. Then 310 mL of the nano-aramid fiber dispersion prepared in step 2 of Example 1 is added thereto, and then 10 mL of deionized water is dropped into the mixed solution, and water bath ultrasonic treatment is performed for 3 hours. Subsequently, the prepared mixed solution is quickly injected into 1000 mL of deionized water to generate a flocculated liquid, and the flocculants are repeatedly washed with a Buchner funnel to filter out residual solvent, and the flocculants are dispersed in 500 mL of deionized water and high-speed sheared at a speed of 12000 rpm for 20 minutes to obtain a dispersed and stable mixed slurry. Finally, the mixed slurry is vacuum filtered with a polytetrafluoroethylene filter membrane until dry, and the filter membrane is removed to obtain a sandwich material.
[0114] Comparative Example 2
[0115] The difference between this comparative example and Example 1 is that step 1 is not included, and step 3 uses aluminum foil with a thickness of 10 μm as the interlayer material and is prepared with the aid of an adhesive.
[0116] The specific preparation process of step 4 is as follows:
[0117] Take two portions of outer layer material slurry exactly the same as in step 4 of Example 1, and vacuum filter them with a polytetrafluoroethylene filter membrane until the slurry is completely dry. After removing the filter membrane, two sheets of outer layer material of the composite insulating paper are obtained, and the aluminum foil as the interlayer material is cut to make it consistent with the shape of the outer layer material, and an acrylic adhesive is evenly applied on both sides thereof. Then, the two sheets of outer layer material are respectively bonded to the two sides of the interlayer material, and the composite aramid insulating paper of this comparative example is obtained after hot pressing.
[0118] Comparative Example 3
[0119] The difference between this comparative example and Example 1 is that mica nanosheets and fluorinated graphene are not included in step 2.
[0120] The performance of the insulating paper obtained in the above embodiment is tested as follows:
[0121] The corona resistance performance test method refers to the current national standard GB / T 22689-2008 "Recommended test method for determining the relative resistance of solid insulating materials to surface discharge breakdown" to conduct thermal aging high-frequency pulse corona resistance duration test.
[0122] The puncture strength and tensile strength tests are carried out in accordance with GB / T 20629.2-2013 "Non-cellulose paper for electrical use Part 2: Test methods"; the electromagnetic shielding effect test of composite insulating paper is based on GB / T 30142-2013 "Measurement method for shielding effectiveness of planar electromagnetic shielding materials".
[0123] from Figure 4and Figure 5 The test results show that the insulation paper obtained in Example 1 of the present invention has better resistance to partial discharge, and its breakdown strength and corona resistance time are significantly better than those of the comparative example. The breakdown strength of Example 1 is better than that of Comparative Example 1 and Comparative Example 2, because the surface of the coaxial nanofiber filaments in the interlayer material of the present invention is aramid fiber, while Comparative Example 1 is exposed high-conductivity carbon nanotubes, and Comparative Example 2 is aluminum foil. Compared with Example 1 and Comparative Example 3, the nano-functional filler in the outer layer material used in the present invention can effectively hinder the generation and development of discharge channels.
[0124] from Figure 6 It can be seen from the electromagnetic shielding results that, compared with the insulating paper obtained in the comparative example, the electromagnetic shielding performance of the insulating paper obtained by the present invention is significantly superior. It can be seen that a carbon nanotube nano-conductive network with excellent electromagnetic shielding performance is constructed in the interlayer material.
[0125] from Figure 7 It can be seen that the thermal conductivity of the insulating paper obtained in Example 1 of the present invention is higher than that of Comparative Examples 1 and 2. The thermal conductivity of the insulating paper obtained in Example 1 is 5.44 W·m -1 K -1 , which is about 1.97 times that of comparative example 3. The outer layer material in the present invention has high thermal conductivity fluorinated graphene and mica nanosheets.
[0126] from Figure 8 It can be seen that the insulating paper obtained by the present invention can withstand stronger mechanical stress than the aluminum foil interlayer of Comparative Example 2, because the similar interface characteristics between the layers of material make their connection more closely.
[0127] The present invention uses a nanofiber felt formed by coaxial nanofibers with meta-aramid fibers as the shell layer and carbon nanotubes as the core layer as the interlayer material. During the hot pressing process (12Mpa, 180°C), the high molecular polymer aramid fibers in the shell layer of the coaxial fiber fibers soften or melt, and the highly conductive and heat-resistant carbon nanotubes in the core layer are mechanically squeezed to contact each other. After returning to normal temperature and pressure, a layered network structure with external electrical insulation and internal high conductivity is formed. Compared with the existing traditional electromagnetic shielding media such as aluminum foil and silver nanowire net, the insulating paper obtained by the present invention does not sacrifice the insulating properties of the insulating paper, so that it has good electromagnetic shielding performance.
[0128] The insulating paper obtained by the present invention uses fluorinated graphene with a particle size of 4 to 8 μm and a thickness of 1 to 2 mm and mica nanosheets with a particle size of 300 to 600 nm and a thickness of 100 to 200 nm as synergistic nanofillers in the outer layer material. Graphene fluoride can significantly improve the thermal conductivity of insulating paper, and its strong electrical insulation properties help to enhance the insulation strength of insulating paper. Mica nanosheets have outstanding local discharge (corona) resistance properties, and being selected as anti-corona functional elements can significantly extend the anti-corona time of insulating paper. More importantly, under the vertical attraction of the vacuum filtration preparation process, these two nanomaterials can achieve a reasonable stacking of "size matching" due to the significant differences in particle size and thickness, thereby constructing a more compact composite structure in the outer layer material of the composite insulating paper. This combination of nanoparticles of different scales can not only effectively fill the gaps between traditional single nanofiller particles and improve the density of the material, but also form a nested structure, which helps to hinder the generation and development of discharge channels, and further improves the insulation, thermal conductivity and other properties of the insulating paper.
[0129] And the outer layer material is composed of aramid nanofibers, mica nanosheets, and fluorinated graphene, wherein the aramid nanofibers are high molecular polymers, the mica nanosheets are aluminum silicate minerals, and the fluorinated graphene is a carbon derivative. The three nanomaterials with different properties and physical scales are stacked and contacted with each other, forming three interfaces in the outer layer material. And because there are a large number of microscopic defects on the surface of the nanoparticles, rich deep traps can be introduced between different interfaces. The deep traps can capture charge carriers and hinder their migration, while forming a shielding electric field opposite to the direction of the applied electric field of the material, thereby improving the breakdown resistance and corona resistance of the insulating paper. The present invention adopts mica nanosheets to cooperate with fluorinated graphene to dope the aramid nanofibers of the outer layer material, while achieving reasonable stacking to build a dense structure, it also introduces rich interfaces and a large number of deep traps into the outer layer material, which plays a role in improving the insulation and corona resistance of the composite insulating paper.
[0130] The insulating paper of the present invention uses a vacuum filtration-assisted high-temperature hot pressing process to tightly combine the interlayer material and the outer layer material, without the need to use any adhesive, and there is no insulation risk of aging and peeling of the adhesive between the electromagnetic shielding layer and the insulating paper substrate of conventional electromagnetic shielding insulating paper. In addition, the interlayer material and the outer layer material in the composite aramid insulating paper provided by the present invention both use nano-aramid fibers as the main material, with consistent interface properties and high affinity, which helps to form a composite insulating paper with a tight interface. Compared with traditional multi-layer electromagnetic shielding insulating paper, its operating life is significantly increased, and the probability of aging and delamination failure is greatly reduced.
[0131] The composite aramid insulation paper obtained by the present invention has excellent electromagnetic shielding performance, and has the advantages of high electrical strength, long corona resistance time, mechanical stress resistance, etc. It can solve the deficiencies and problems of electromagnetic shielding insulation paper such as traditional aluminum foil interlayer in terms of breakdown strength and corona resistance, and is adapted to the development needs of current advanced power electronic devices and electrical equipment.
Claims
1. A method for preparing a high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper, characterized in that: The following steps are involved: Step 1: Using meta-aramid fiber as the shell layer and carbon nanotube as the core layer, coaxial nanofiber filaments are obtained by coaxial electrospinning; Step 2: fully mixing mica nanosheets, fluorinated graphene and meta-nano aramid fibers in a solvent to obtain a mixed slurry; the mass ratio of the mica nanosheets, fluorinated graphene and meta-nano aramid fibers is 0.1-0.3:0.1-0.2:1; Step 3: preparing a nanofiber felt using the coaxial nanofibers obtained in step 1; Step 4: Using the nanofiber felt obtained in step 3 as the interlayer material and the mixed slurry as the surface material, a multilayer structure material is formed by vacuum filtration, wherein the upper and lower surfaces of the interlayer material are covered with the surface material; Step 5: hot-press the multilayer structure material obtained in step 4 to obtain the desired composite aramid insulation paper.
2. The method for preparing a high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper according to claim 1, characterized in that: In the step 1, the diameter of the coaxial nanofiber filament is 200-600 nm, and the ratio of the radius of the core layer to the thickness of the shell layer in the coaxial nanofiber filament is 2-5:8-5.
3. The method for preparing a high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper according to claim 1, characterized in that: The intermediate aramid fiber in step 1 needs to be pretreated before use: Cutting the meta-aramid fibers into short fibers of 5 to 10 mm; The chopped fibers were ultrasonically treated in acetone, then vacuum filtered and rinsed three times, and then dried. After drying, the fibers were dissolved in a LiCl solution to obtain a meta-aramid fiber solution.
4. The method for preparing a high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper according to claim 1, characterized in that: The preparation method of mica nanosheets in step 2 is as follows: Adding mica powder to the intercalant solution, and obtaining a mica dispersion after ultrasonic treatment; The mica dispersion was heated at 100°C for 6 hours; after centrifugal rinsing, it was dried under vacuum conditions; The preparation process of meta-nano aramid fiber is as follows: Cutting the meta-aramid fibers into short fibers of 5 to 10 mm; The chopped fibers were ultrasonically washed in acetone, then vacuum filtered and rinsed three times, and then dried; The dried meta-aramid fiber is dissolved in a strong alkaline solution, fully stirred, and subjected to ultrasonic dispersion treatment.
5. The method for preparing a high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper according to claim 1, characterized in that: The mixed slurry preparation process in step 2 is as follows: Add mica nanosheets and fluorinated graphene into the solvent dimethyl sulfoxide and perform water bath sonication; adding meta-nano aramid fiber dispersion; Deionized water is dropped into the mixed solution, and ultrasonic treatment is performed in a water bath to obtain a mixed solution; The mixed solution after ultrasonication is injected into deionized water to generate floccules; The flocculants are dispersed in deionized water and sheared at high speed to obtain a dispersed and stable mixed slurry.
6. The method for preparing a high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper according to claim 1, characterized in that: In step 4, the mass ratio of the surface layer material to the interlayer material is 7-9:3-1.
7. The method for preparing a high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper according to claim 1, characterized in that: The hot pressing process in step 5 is as follows: First, hot pressing was performed at a pressure of 12 MPa and a temperature of 180°C for 6 min; Then, the pressure was maintained at 12 MPa at room temperature for 2 min.
8. The high thermal conductivity, corona-resistant, electromagnetic shielding composite aramid insulation paper obtained by any one of claims 1 to 7, characterized in that: The composite aramid insulation paper is a composite sandwich structure formed by hot pressing with the upper and lower surfaces of the sandwich material covered with the outer layer material; The sandwich material is a composite nanofiber felt prepared by coaxial nanofiber filaments obtained by coaxial electrospinning, with meta-aramid fibers as the shell layer and carbon nanotubes as the core layer; The outer layer material is a mixed slurry obtained by fully mixing and dispersing mica nanosheets, fluorinated graphene and meta-nano aramid fibers.
9. The high thermal conductivity and corona resistant electromagnetic shielding composite aramid insulation paper according to claim 8, characterized in that: The carbon nanotube has a length of 0.4-5 μm and a diameter of 8-20 nm; the mica nanosheet has a particle size of 300-600 nm and a thickness of 100-200 nm; the fluorinated graphene has a single-layer structure, a fluorine-carbon ratio of 1:1, a particle size of 4-8 μm and a thickness of 1-2 nm.
10. The use of the high thermal conductivity corona resistant electromagnetic shielding composite aramid insulation paper according to any one of claims 8 to 9, characterized in that: The composite aramid insulation paper is used for preparing insulation components of power transformers.
Citation Information
Patent Citations
Fluorinated carbon nanotube / aramid nanofiber composite insulation paper and preparation method thereof
CN116024840A
Corona-resistant N-grade insulation paper for variable frequency motor and preparation method of corona-resistant N-grade insulation paper
CN116892129A
Aramid insulation paper and preparation method and application thereof
CN118704267A
Composite aramid insulation paper and preparation method thereof
CN118958051A
KR20240103921A